OLDEST TRIASSIC NAUTILINA - Dagis A.S.; Sobolev Ye.S. (My University, 1989)
The Cenoceras fauna of the Upper Triassic Notal basins has been considered the oldest, which gave rise to all other younger Nautilina. It is the only Triassic genus that crossed the Triassic-Jurassic boundary and survived into the Jurassic. Recently, older specimens of true Nautilina, also belonging to the genus Cenoceras, have been found in Boreal regions. They come from the Lower Carnian deposits (Discophyllites taimyrensis beds) of Cape Tsvetkov in the Eastern Taymyr region. The Siberian forms, which belong to the new species C. boreale, can be likened only to the genus Cenoceras, widespread in the Liassic. The chronology of the oldest Nautilina is not fully clear. The genus Cenoceras probably first appeared in the Boreal basins and in the Late Triassic most likely had a bipolar distribution. In the Liassic it remained only in the Boreal basins of Europe and Siberia.
Keywords: Triassic; Мезозой::Триасовая; Mesozoic::Triassic